Effect of Aspirin on Activities of Daily Living Disability in Community-Dwelling Older Adults. (26th December 2020) - Woods, Robyn L; Espinoza, Sara; Thao, Le T P; Ernst, Michael E; Ryan, Joanne; Wolfe, Rory; Shah, Raj C; Ward, Stephanie A; Storey, Elsdon; Nelson, Mark R; Reid, Christopher M; Lockery, Jessica E; et al.
Abstract: Background: Cerebrovascular events, dementia, and cancer can contribute to physical disability with activities of daily living (ADL). It is unclear whether low-dose aspirin reduces this burden in aging populations. In a secondary analysis, we now examine aspirin's effects on incident and persistent ADL disability within a primary prevention aspirin trial in community-dwelling older adults. Methods: The ASPREE (ASPirin in Reducing Events in the Elderly) trial of daily 100 mg aspirin versus placebo recruited 19 114 healthy adults aged 70+ years (65+ years if U.S. minority) in Australia and the United States. Six basic ADLs were assessed every 6 months. Incident ADL disability was defined as inability or severe difficulty with ≥1 ADL; persistence was confirmed if the same ADL disability remained after 6 months. Proportional hazards modeling compared time to incident or persistent ADL disability for aspirin versus placebo; death without prior disability was a competing risk. Results: Over a median of 4.7 years, incident ADL disability was similar in those receiving aspirin (776/9525) and placebo (787/9589) with walking, bathing, dressing, and transferring the most commonly reported. Only 24% of incident ADL disability progressed to persistent. Persistent ADL disability was lower in the aspirin group (4.3 vs 5.3 events/1000 py; hazard ratio [HR] = 0.81, 95% confidence interval [CI]: 0.66–1.00), with bathing and dressing the most common ADL disabilities in both groups. Following persistent ADL disability, there were more deaths in the aspirin group (24 vs 12). Discussion: Low-dose aspirin in initially healthy older people did not reduce the risk of incident ADL disability, although there was evidence of reduced persistent ADL disability.